ABO Blood Type Examination in Pregnant Women with Anemia at The Nayaka Husada Clinic in 2026 - Desy Lustiany Rajagukguk; Sofiani Sari; Siti Hardianti; Dicky Yuswardi (Institut Kesehatan Medistra Lubuk Pakam, 2026)
Anemia is a clinical condition characterized by a reduced number of erythrocytes, so that the blood's ability to distribute oxygen to body tissues is not optimally fulfilled. According to the World Health Organization (2023), approximately 30% of women aged 15–49 years (around 571 million) and 40% of children aged 6–59 months (269 million) are affected by iron deficiency anemia. The risk of anemia increases with advancing gestational age, particularly among women from lower socioeconomic backgrounds. The prevalence of anemia in Indonesian pregnant women has reached 48.9% in 2020, approaching the threshold for a severe public health problem (≥40%). This study was conducted at Nayaka Husada Clinic, Duri, in March 2026, aiming to determine the distribution of ABO blood group systems among pregnant women with anemia. The study subjects consisted of 20 capillary blood samples analyzed using the Easytouch Hb device. The results indicated that 2 respondents (10%) had normal hemoglobin levels, while 18 respondents (90%) exhibited decreased hemoglobin levels. The distribution of anemia cases based on blood groups revealed that blood group B had the highest proportion, with 8 individuals (40%). This was followed by blood group O with 6 individuals (30%) and blood group A with 5 individuals (25%). The lowest proportion was observed in blood group AB, with only 1 individual (5%). These findings suggest that the prevalence of anemia among pregnant women is higher in individuals with blood group B.